PENGARUH SUHU PADA DAYA KELUARAN MODUL FOTOVOLTAIK DENGAN PENAMBAHAN REFLEKTOR DI SAMARINDA - Suratno Suratno (Lembaga Penelitian Universitas Balikpapan, 2020)
The heat that occurs in photovoltaic modules is significantly affected by environmental conditions and the installation of photovoltaic panels. The addition of a reflector can increase surface temperature and further increase output power. In general, the high working temperature in photovoltaics can reduce the value of output power production. However, there were two phenomena when testing in Samarinda, which are 7th- and 8th phenomena. The 7th phenomenon occurs when the surface temperature rises, the output power will rise. Meanwhile, the 8th phenomenon happens when the surface temperature rises, the output power decreases. The distribution pattern of these phenomenon shows that the 7th phenomenon occurs twenty times, while the eighth phenomenon occurs twenty-five times with an even distribution pattern. Moreover, the 8th phenomenon is more common than the 7th phenomenon during five days of observation.